Role of the cerebellum in postural control - Dai Yanagihara (Japanese Society of Physical Fitness and Sports Medicine, 2014)
In daily life, voluntary movements accompany the appropriate whole-body configurations and orientations in relation to the force of gravity. To produce skilled motor behavior, it is necessary to concurrently maintain an upright stance. There are two main aspects to postural control, namely, compensatory postural reaction by means of sensory feedback mechanisms, and anticipatory postural adjustments by means of feedforward mechanisms. The cerebellum has been suggested to be the brain region principally responsible for these postural control mechanisms. In this report, we review the effects of lesions of the cerebellum on postural control in human patients and in a mouse model of a human inherited disease.